Mejoramiento de los procesos de administración de vehículos y transporte de la Universidad Técnica Estatal de Quevedo por medio de software - Rodriguez Veloz, Andrea Fernanada (2015)
Web application management of vehicles and transport Quevedo State Technical University, which facilitates the mobilization of personnel management that makes use of these, according to production activities, academic, scientific and appropriate linkage was performed. This web application streamlines the process of assigning vehicles to institutional committees, decreasing the time distribution of drivers for different vehicles, avoiding redundancy and place to assign. For the creation of the website, free and platform-independent software was used as XAMPP, an Apache server that contains the packages MySql database that was implemented for recording and accessing transport and its committees, PHP , Perl and java tools that were used to program once established the analysis and design of the website. The RUP (Rapid Software Development Process) methodology is the fundamental basis for the analysis, implementation and documentation of this thesis, to assess the outcome of the general hypothesis quasi-experimental method that allowed measuring the allocation of vehicles used with pre-tests and post-tests using the web application. The results of the quasi - experimental tests of the above analysis were checked through the analytical method a significant difference in reduction of conflicts in the availability of vehicles and drivers, as well as the proper handling of your legal documents and reducing time to obtain n travel reports